Desarrollo sostenible, capital social y empoderamiento en la democracia latinoamericana - Baquero, Marcello (2007)
One of the paradoxes of Latin American contemporary societies is the asymmetry between economic development and modernization on one hand, and stagnation and decrease of the quality of democracy when thought in its subjective and social dimension, that is, when we take in to account citizens material conditions. Understanding the reasons of this dilemma is the main objective of this article. Initially the paper suggests that the analysis of democracy in our continent requires going beyond minimalists conceptions, this, incorporating the social dimension. As a result we suggest alternative ways in the construction of a more protagonic politicol culture.